Lower Eocene sedimentary succession and microfossil biostratigraphy in the central northern Caucasus basin - E. Shcherbinina; A. Iakovleva; Y. Gavrilov; O. Golovanova; N. Muzylev (Geologica Acta, 2020)
The lower Eocene sediments from the classical Paleogene section exposed along the Kheu River, northern Caucasus, southern Russia are here studied. This ca. 50m thick succession is lithologically contrasting: the lower and upper parts are composed by soft marls separated by a thick Radiolaria-rich unit of non-calcareous and low-calcareous mudstones with intercalations of compact cherty layers. According to nannofossil and dinocyst biostratigraphy, the unique intercalation of Total Organic Carbon (TOC)-rich sediment (sapropelitic bed) in the lower part of the lower Eocene correspond to the Paleocene-Eocene Thermal Maximum (PETM) and a series of sapropelitic interlayers in the upper marly part of the lower Eocene succession correlates with the Early Eocene Climatic Optimum (EECO). The study of nannofossil and dinocyst assemblages enabled detailed zonal subdivision and first-order calibration of nannofossil and dinocyst bio-events during this time-span. The studied interval of the section embraces the complete succession of nannofossil zones NP9-NP13 of Martini, 1971, CP8-CP11 of Okada and Bukry, 1980 and CNP11-CNE5 of Agnini et al., 2014. By means of dinocyst stratigraphy, the succession of Apectodinium hyperacanthum, Axiodinium augustum, Deflandrea oebisfeldensis, Dracodinium astra, Stenodinium meckelfeldense, Dracodinium varielongitudum, Ochetodinium romanum/Samlandia chlamydophora and Areosphaeridium diktyoplokum zones are identified in the Ypresian part of the Kheu section.